Public Service Performance at the Siniu District Office, Parigi Moutong Regency (Case Study on Land Surrender Letter Issuance) - Wirda; Pageno, Isbon; Yunus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
The purpose of this research is to understand the Public Service Performance at the Siniu District Office, Parigi Moutong Regency (Case Study on Land Surrender Letter Issuance). The research method used by the researcher is a qualitative research method with a descriptive approach. The data collection technique for informants uses a purposive technique, where data is collected through informants accompanied by observation, interviews, and documentation techniques. Based on the research results, it shows that the Public Service Performance at the Siniu District Office, Parigi Moutong Regency (Case Study on Land Surrender Letter Issuance) has been running well, but there are still some indicators that cannot be considered good. This is seen from the indicators of Work Quality, Quantity, Timeliness, Effectiveness, and Independence, which have not been running well. Since there is still one indicator that has not been running well in terms of Timeliness, it is advisable to emphasize more to the officials about the implementation of the Standard Operating Procedures (SOP) so that the officials work according to the established rules and working hours and are able to increase the effectiveness and quantity of land surrender letter issuance at the Siniu District Office, Parigi Moutong Regency.